UNDERSTANDING THE PURPOSE, FUNCTIONS, AND APPROACHES OF STUDENT AFFAIRS MANAGEMENT - Amin, Nurul; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose and function of student affairs management is to regulate all student activities so that these activities can support the learning process in educational institutions to run smoothly, orderly, and regularly so that they can contribute to the achievement of school goals. Student affairs management is a structuring or arrangement of all aspects of activities related to students, from the entry of students (students) to the exit of students (students) from a school or an educational institution